Sosialisasi PPN atas Perdagangan E-Commerce di Kota Pontianak - Nugraheni, Dyah Novia; Parmawati, Sih (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2025)
The Community Service Program (PKM) themed “Tax Update: Socialization of Value Added Tax (VAT) on E-Commerce Transactions in Pontianak City” was conducted to improve tax literacy and raise public awareness of digital VAT obligations. The background of this activity is the rapid growth of e-commerce and the limited understanding of VAT regulations. The methods included delivering presentations, interactive discussions, and evaluation through questionnaires completed by 66 participants. The evaluation focused on four variables: tax understanding, tax socialization, taxpayer compliance, and VAT revenue. The results showed that participants’ tax understanding was categorized as Good (4.32), tax socialization as Very Good (4.52), taxpayer compliance as Good (4.37), and VAT revenue as Very Good (4.54).In conclusion, this PKM activity effectively enhanced the knowledge and tax awareness of the people of Pontianak, while also encouraging stronger commitment to contributing to state revenue through compliance with e-commerce VAT.